Effect of Addition of Tertiary-Butyl Hydroquinone into Palm Oil to Reduce Wear and Friction Using Four-Ball Tribotester. Issue 5 (2nd September 2016) - Sapawe, N.; Samion, Syahrullail; Zulhanafi, P.; Nor Azwadi, C. S.; Hanafi, M. F.
ABSTRACT: Replacing mineral oil with vegetable oils as lubricants continues to attract interest due to their environmentally friendly characteristics and ease of disposal. However, one disadvantage can be low thermal oxidative stability. The purpose of our research is to investigate the ways in which oxidation can be contained by combining palm oil with a phenolic antioxidant. A homogeneous mix of palm oil and tertiary-butyl hydroquinone was found to exhibit satisfactory antioxidant properties and reduce wear and friction. Superior mineral engine oil was used to benchmark the performance.